Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1248/bpb.31.1008
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Serum-Free Mouse Embryo Cells into an Astrocytic Lineage is Associated with the Asymmetric Production of Early Neural, Neuronal and Glial Markers

Abstract: Serum-free mouse embryo (SFME) cells, the astrocyte progenitor cells in the central nervous system (CNS), were exposed to 10 ng/ml leukemia inhibitory factor (LIF) and 10 ng/ml bone morphogenic protein 2 (BMP2) to induce differentiation, and expression of cell-type specific markers. Nestin, a marker of early neural lineage, b bIII-tubulin, a marker of neuronal lineage, oligodendrocyte marker O4 (O4), a marker of oligodendrocytic lineage and glial fibrillary acidic protein (GFAP), a marker of astrocytic lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…For F-actin labeling, cells were incubated with rhodamine-phalloidin. As previously reported, 12) the anti-bIII-tubulin antibody in the present study showed appropriate specificities (data not shown). For bIIItubulin labeling, cells were blocked in Tris-buffered saline containing 0.05% Tween-20 and 3% non-fat dried milk.…”
Section: Methodssupporting
confidence: 90%
“…For F-actin labeling, cells were incubated with rhodamine-phalloidin. As previously reported, 12) the anti-bIII-tubulin antibody in the present study showed appropriate specificities (data not shown). For bIIItubulin labeling, cells were blocked in Tris-buffered saline containing 0.05% Tween-20 and 3% non-fat dried milk.…”
Section: Methodssupporting
confidence: 90%
“…Many reports show that astrocytes express ion channels, both ligand-gated and voltage-dependent [1], have the general functions of clearing neurotransmitters and ions away from the synapse [2, 3] and more direct and active roles in synapse function [4, 5]. There also are some reports showing that astrocytes play an important role in regulating the function of oligodendrocytes [6, 7] and neural stem cells [8, 9]. …”
Section: Astrocyte and Astrogliosismentioning
confidence: 99%